The New Regulation of the Monastery of Saint John the Theologian in Patmos (Kanon, 2014)
ΚΑΝΟΝ ΧΧΙΙ, Jahrbuch der Gesellschaft fur das Recht der Ostkirchen, Partilularrecht. ed. Roman Kovar, Hennef 2014